Analisis Tegangan Support pada Pipa Exhaust Main Engine - Sebrina Sidqi Shavira; Fipka Bisono; Budianto Budianto (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
Abstract – The KRSB ship is a hospital ship made by one of the shipping manufacturing companies in Surabaya. On the ship there is a main engine that has an exhaust system. The exhaust system consists of several components, one of which is the exhaust pipe. The exhaust pipe will be subjected to vibration due to resonance from the main engine. So it is necessary to design a support for the exhaust pipe that is strong and not deformed to support all types of loading. An analysis of the stresses acting on the supports was performed using the Fusion 360 student version software. In this study, we obtained a design drawing that can be used as an alternative in installing supports on the exhaust pipe. In this study, 3 variations of the strut installation were selected. The first concept are choosen, which consists of 9 supports, it has the highest score in the Ulrich concept assessment. Safety factor value is 2.87, capable of receiving a voltage of 60.66 MPa.